Actor Interventions in Influencing Education Policy Formulation: A Case Study on Integrated Curriculum Formulation - Nur Hafni; Aiyub Aiyub; Ainol Mardhiah; Muryali Muryali; Fauzi Fauzi (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
This study analyzes the education policy process formulated by the actors. The specific purpose of this research seeks to reveal and analyze how the official actors (state actors) and informal actors (non-state actors). The research method used is a qualitative method with a study case approach. The results show that the problem of intervention by formal actors is still very serious to persuade integrated curriculum, it affects the synergy of collaboration between formal and informal actors, so that the integrated curriculum programs are formulated give rise to different interpretations and meanings between implementing agencies. A policy of providing education does not reflect the privileges of Acehnese education. The research findings indicate that there is no derivative policy that regulates the formulation of an Islamic values-based curriculum in more detail. Actor analysis and typology of political strategy, namely positional strategy; power; player; and perception strategies, are used in this research. In addition, this research is expected to overcome the ignorance of various parties regarding the process behind the formation of a policy and the implications of the unrealized implementation of Islamic values-based Aceh education.